Understanding the Relationship Between Second Language Teacher Beliefs and Their Instructional Practices: A Case Study of Core French Teachers - Viswanathan, Usha (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2019)
This study explores the relationship between Core French teachers’ beliefs and their instructional practices. In the literature, contextual elements, as well as the compatibility between teacher beliefs and second language teaching approaches such as communicative language teaching (CLT) have been regularly cited as key factors contributing to discrepancy between beliefs and practices. However, these factors did not adequately explain what I had witnessed as a teacher educator. To explore this topic, data were gathered via questionnaire, observations, and individual interviews on the beliefs and practices of Core French teachers in the Toronto, Ontario region. In analyzing the data through the lens of a hybrid framework of complexity theory and the theory of self-efficacy, small differences in how teachers handled chaos, the term used in complexity theory to describe periods of instability in non-linear systems such as Core French classrooms, were found to be a key factor in explaining discrepancies between beliefs and practices. Moreover, levels of self-efficacy were found to influence how teachers handled chaos. Findings also revealed important differences in outcome (e.g., teacher and student comfort with and use of the target language) in classes taught by teachers with a high degree of self-efficacy versus those with lower levels of self-efficacy.